2012
DOI: 10.1136/emermed-2011-200298
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric trauma patients and attention deficit hyperactivity disorder: correlation and significance

Abstract: The data suggest that children who make repeated trauma-related ED visits have a predisposition to ADHD, and they may benefit from screening for this disorder while in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
(24 reference statements)
2
17
0
Order By: Relevance
“…Few of the studies on association of ADHD and injuries were case-control studies which assessed the ADHD status through rating scales such as Conner’s scales. 13 , 16 , 24 - 26 Regardless of the variety in rating scales used by different studies, the point in such assessment is that these studies just assess the association of the ADHD rating score with injuries rather than association of ADHD and injuries unless a cutoff point is used to dichotomize the score or the patients with higher scores are later assessed for the diagnosis of ADHD through clinical interviews done by a psychiatrist. However, the research question may also be different whether people with higher scores, regardless of their final diagnosis, are at higher risk of injuries or not.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the studies on association of ADHD and injuries were case-control studies which assessed the ADHD status through rating scales such as Conner’s scales. 13 , 16 , 24 - 26 Regardless of the variety in rating scales used by different studies, the point in such assessment is that these studies just assess the association of the ADHD rating score with injuries rather than association of ADHD and injuries unless a cutoff point is used to dichotomize the score or the patients with higher scores are later assessed for the diagnosis of ADHD through clinical interviews done by a psychiatrist. However, the research question may also be different whether people with higher scores, regardless of their final diagnosis, are at higher risk of injuries or not.…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies have examined the rates of accidents and injuries in children with ADHD, it has been stated that these studies were mostly carried out in the USA and that their results could not be generalized to other cultures [10]. However, studies in Europe [17] and in Turkey also showed that ADHD may make children more vulnerable to accidents [26]. Nevertheless, there is a different limitation to studies already conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterised by hyperactivity, impulsivity, and cognitive dysfunction [1,2]. ADHD often causes major negative impact in one's daily life and generally patients with ADHD are more prone to injuries including motor vehicle accidents, fractures and brain injuries [3]. Risk of injury to children and adolescents with ADHD might be mediated by several factors, such as impairment of motor functions, developmental coordination disorders or other core symptoms [4].…”
Section: Introductionmentioning
confidence: 99%